2018
DOI: 10.3389/fimmu.2018.02088
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by Processed Animal Feed: The Role of Maillard Reaction Products and Advanced Glycation End-Products (AGEs)

Abstract: The immune system provides host protection to infection with pathogenic organisms, while at the same time providing tolerance upon exposure to harmless antigens. Thus, an impaired immune function is associated with increased susceptibility to infections with increased disease severity and thereby necessitating the therapeutic use of antibiotics. Livestock performance and feed efficiency, in addition to their health status, are dependent on the microbial load of their gut, the barrier function of the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 180 publications
(186 reference statements)
0
24
0
2
Order By: Relevance
“…A standard autoclave protocol for sterilizing grain-based diets increased the concentration of the commonly assessed AGEs, CML, and the dicarbonyl precursor of AGEs, MG. It should be noted that the CML and MG content of the Non-AC diets was not zero, as all pelleted food undergoes extrusion and drying with heat and this may set a "baseline" dietary AGE concentration [11]. Importantly, we found that the higher dietary AGEs concentration varied depending on the location within the autoclave, where the highest concentrations of CML and MG were found near the heat source in the autoclave.…”
Section: Discussionmentioning
confidence: 69%
“…A standard autoclave protocol for sterilizing grain-based diets increased the concentration of the commonly assessed AGEs, CML, and the dicarbonyl precursor of AGEs, MG. It should be noted that the CML and MG content of the Non-AC diets was not zero, as all pelleted food undergoes extrusion and drying with heat and this may set a "baseline" dietary AGE concentration [11]. Importantly, we found that the higher dietary AGEs concentration varied depending on the location within the autoclave, where the highest concentrations of CML and MG were found near the heat source in the autoclave.…”
Section: Discussionmentioning
confidence: 69%
“…The degree of the browning development was governed by several factors, especially temperature–time regime and types, concentration and ratio of reactants (Ajandouz et al ., 2001; Ajandouz et al ., 2008). The Maillard reaction is correlated well with the reaction temperature and time (Teodorowicz et al ., 2018; Asghar et al ., 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, nipa palm syrup shows some free radical scavenging activity. This free radical scavenging activity can be improved via the Maillard reaction, which is a nonenzymatic glycation reaction (Zhang et al ., 2009; Teodorowicz et al ., 2018; Asghar et al ., 2020a). However, thermal Maillard reaction had a detrimental effect on the colour of the final syrup because dark syrup could be rejected by consumers (Jiang et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary AGEs have previously been described as potent ligands for a number of cell surface receptors expressed on APCs including RAGE, CD36 and the extracellular unit of the AGE-R complex galectin-3 [ 42 ]. However, the knowledge on the particular binding sides of these receptors to MR-modified proteins is very limited because of complexity of the structural rearrangements during the heat treatment and glycation.…”
Section: Discussionmentioning
confidence: 99%